Vedānta without māyā? : a debate on Saptavidha-anupapatti = Māyāvirahitaḥ Vedāntaḥ? Saptavidhānupapattiviṣaye vādaḥ - Mishra, Godabarisha
Contributed research papers presented at National Seminar on "Saptavidha-anupapatti" , held during August 18-20 , 1998, organized by Indian Council of Philosophical Research at Chennai, India.